Keberkesanannya Pengurusan Kreativiti dan Inovasi Pendidikan Matematik - Nor Ahmad, Hj. Abdul Rahim (1997)
This research is on the management of creativity and innovation of mathematics education at several rural area secondary schools in the district of Raub, Pahang Darul Makmur. The purpose is to determine and analyze the functions of management of creativity and innovation in mathematics education towards building mathematics culture among students in rural area secondary school. The findings show that there exists a significant relationship between management of creativity and innovation in mathematics culture. Several recommendations are made to enhance the efforts in building mathematics culture among students in rural area. The purpose is to enable rural area secondary school students acquire adequate knowledge and skills in mathematics, science and technology to achieve the targets in Vision 2020.